Blogging - Orr, Tamra (Global citizens: social media., 2019)
Explores the history of blogging looking back on the first known diaries and the rise of online journaling. Explores legal issues related to blogging such as libel and copyright concerns, and highlights how an income can be generated from a blog. Includes resources for further information, a glossary, and color photographs.